Mediating effect of work-life balance towards leadership style and work engagement - Valentina Happy Vanesa; Dewi Shanty; Triyani Triyani; Andreas Wahyu Gunawan P; Stefanus M S Sadana; Dadang Supriatna (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The dynamism of the current work environment, especially for ASN Bandung Regency, makes the government need employees who provide quality and timely services as a form of satisfaction and community expectations. For that, leaders must understand the most suitable leadership style to be applied by government employees. The leadership style for employees who work from home (WFA) is expected to increase work engagement through work-life balance in the organization. This study uses Structural Equation Modeling (SEM) with 500 respondents from Bandung Regency ASN employees. The purpose of this study was to analyze the work-life balance mediating the effect of transformational leadership, transactional leadership, and servant leadership on the work engagement of Bandung Regency Government employees. The population of this research is the government employees of Bandung Regency . The sampling technique used is simple random sampling. Findings: The leadership styles in the organization owned by the head of ASN in Bandung Regency to increase work engagement through work-life balance are transactional leadership and servant leadership. Originality/values: In one study, analyzing work-life balance mediates the effects of transformational leadership, transactional leadership, and servant leadership on work engagement.